Integrated Study of Dust-air Pollution Interaction over the Eastern Mediterranean - Abdelkader, Mohamed M; Metzger, Swen M.; Klingmüller, K.; Mamouri, Rodanthi-Elisavet; Astitha, Marina; Hadjimitsis, Diofantos G.; Barrie, Leonard A.; Levin, Zev; Lelieveld, Jos (My University, 2015)
Interactions of desert dust and air pollution over the Eastern Mediterranean (EM) have been studied, focusing on two distinct dust transport events on 22 and 28 September 2011. The atmospheric chemistry-climate model EMAC has been used at about 50 km grid spacing on global scale, applying an online dust emission scheme and calcium as a proxy for dust reactivity. EMAC includes a detailed tropospheric chemistry mechanism, aerosol microphysics and thermodynamics schemes to describe dust" aging''. The model is evaluated using ground-based observations for aerosol concentrations and aerosol optical depth, LIDAR as well as satellite observations. Simulation results and back trajectory analysis show that the development of synoptic disturbances over the EM can enhance dust transport from the Sahara and Arabian deserts in frontal systems that also carry air pollution to the EM.
Keywords: Dust-air pollution; Interaction; Eastern Mediterranean